2015
DOI: 10.1080/10408398.2013.769934
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Methods and Techniques for Freshness Quality Determination and Evaluation of Fish and Fish Fillets: A Review

Abstract: The freshness quality of fish plays an important role in human health and the acceptance of consumers as well as in international fishery trade. Recently, with food safety becoming a critical issue of great concern in the world, determination and evaluation of fish freshness is much more significant in research and development. This review renovates and concentrates recent advances of evaluating methods for fish freshness as affected by preharvest and postharvest factors and highlights the determination method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
85
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(88 citation statements)
references
References 131 publications
0
85
0
3
Order By: Relevance
“…The K value was originally defined by Saito et al (1959) and has been one of the most effective indicators of the freshness of fish. Although many chemical methods can be employed to evaluate fish freshness, including moisture measurement, volatile compounds measurements, protein changes, and lipid oxidation (Cheng et al 2013), ATP-related compounds often give the best results in the time frame before significant microbial spoilage occurs. Hamada-Sato et al (2005) indicated that the quality of raw fish"sashimi" could be judged based on the K value rather than histamine.…”
Section: Use Of Atp-related Compounds As a Freshness Indicatormentioning
confidence: 99%
“…The K value was originally defined by Saito et al (1959) and has been one of the most effective indicators of the freshness of fish. Although many chemical methods can be employed to evaluate fish freshness, including moisture measurement, volatile compounds measurements, protein changes, and lipid oxidation (Cheng et al 2013), ATP-related compounds often give the best results in the time frame before significant microbial spoilage occurs. Hamada-Sato et al (2005) indicated that the quality of raw fish"sashimi" could be judged based on the K value rather than histamine.…”
Section: Use Of Atp-related Compounds As a Freshness Indicatormentioning
confidence: 99%
“…Indeed, physicochemical and instrumental (Boonsumrej, Chaiwanichsiri, Tantratian, Suzuki, & Takai, 2007;Okpala, Choo, & Dykes, 2014;Ramos, Gomide, Ramos, & Alexandre Peternelli, 2004), sensory (Erickson et al, 2007;Tsironi et al, 2009), microbiological (Canizales-Rodríguez et al, 2013Pinu, Yeasmin, Bari, & Rahman, 2007) and some other methods have proved to be available and effective, which, however, possess the weakness of low speed, inefficiency, time and labor consuming as well as high expenditure (Cheng, Sun, Zeng, & Liu, 2013). Ahmad, Jeenanunta, Chanvarasuth, and Komolavanij (2014) attempted to predict the quality characteristics of frozen shrimp by genetic algorithm-neural network model, i.e., GANN, which employs an artificial neural network (ANN) as a main modeling tool and a genetic algorithm GA to optimize the ANN weights, or in some other cases (Tong & Mintram, 2010) to train the model by inputting the variables of freezing rate, thawing rate, storage time, and sizes of frozen shrimp.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, determination of fish freshness is obviously essential for food quality and safety control. Currently, some methods and techniques developed to measure and evaluate fish freshness are mainly related to sensory evaluation, examining physical properties (colour and texture), microbial methods, measuring volatile compounds and lipid oxidation, determining changes in muscle proteins, and ATP breakdown products in fish (Cheng, Sun, Han, & Zeng, 2014;Cheng, Sun, Zeng, & Liu, 2013;Cheng & Sun, 2015). Among them, as an important evaluation method, sensory evaluation offers the most satisfactory means of assessing the freshness quality of fish and is commonly used in the fish sector and inspection services to provide the best valid consumer acceptability (Barbosa & Vaz-Pires, 2004).…”
Section: Introductionmentioning
confidence: 99%